Obliterative (Constrictive) Bronchiolitis - Lynch, Joseph P., III; Weigt, S. Samuel; DerHovanessian, Ariss; Fishbein, Michael C.; Gutierrez, Antonio; Belperio, John A. (Seminars in Respiratory and Critical Care Medicine, 2012)
Obliterative bronchiolitis (OB) (formerly termed bronchiolitis obliterans), is a rare fibrotic disorder involving terminal and respiratory bronchioles. The term constrictive bronchiolitis is synonymous with OB. Clinically, OB is characterized by progressive (often fatal) airflow obstruction, the absence of parenchymal infiltrates on chest radiographs, a mosaic pattern of perfusion on high-resolution computed tomographic scan, poor responsiveness to therapy, and high mortality rates. Most cases of OB occur in the context of a specific risk factor. Currently, most cases of OB occur in lung transplant recipients with chronic allograft rejection or hematopoietic stem cell transplant (HSCT) recipients with graft versus host disease (GVHD). Other causes of OB include connective tissue disease (CTD) (particularly rheumatoid arthritis); lower respiratory tract infections; inhalation injury; exposure or inhalation of toxic fumes, metals, dusts, particulate matter, or pollutants; occupational exposures; drug reactions; consumption of uncooked leaves of Sauropus androgynus; chronic hypersensitivity pneumonia; diffuse neuroendocrine cell hyperplasia; miscellaneous. When no cause is identified, the term cryptogenic obliterative bronchiolitis is used. This review discusses the salient clinical, radiographic, and histological features of OB and presents a management approach.
Keywords: bronchiolitis obliterans; obliterative bronchiolitis; constrictive bronchiolitis; bronchiolitis obliterans syndrome; chronic lung allograft rejection; hematopoietic stem cell transplant